Octadecyl Amine Functionalized Graphene Oxide towards Hydrophobic Chemical Resistant Epoxy Nanocomposites. Issue 25 (3rd July 2018) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Arjmand, Mohammad; Amani, Ali Mohammad; Sharif, Farbod; Jahandideh, Sara
Abstract: In this research study, graphene oxide (GO) was synthesized using an improved Hummers method and thence oxygen‐based functional groups were replaced with octadecyl amine. Afterwards, epoxy‐based nanocomposites containing GO and GO‐octadecyl amine (GO‐ODA) were fabricated via a vacuum shock technique. The chemical resistance of the fabricated nanocomposites against various solvents, namely xylene, toluene and distilled water, was investigated and the effect of chemical degradation on the hardness and structural stability of the nanocomposites was examined. Besides, SEM, contact angle and AFM analyses were conducted to evaluate morphology, hydrophobicity and roughness of the nanocomposites prior to and following the chemical degradation. The obtained results illustrated that the reinforcement of the epoxy‐based nanocomposites with GO‐ODA and GO, in order, enhanced chemical resistance, hardness, roughness, and hydrophobicity of the nanocomposites. For instance, after incorporating GO and GO‐ODA into the epoxy resin, the average roughness of the neat epoxy resin reduced 84.0% and 94.1%, the hardness of the neat epoxy resin increased from 80 to 82 and 86 kgf/mm 2, and the contact angle of the epoxy resin changed from 76° to 71° and 85°, respectively. In brief, outcome of this study reveals that GO‐ODA can be used as an efficient filler to develop effective hydrophobic polymeric shields against chemical degradation. Abstract : Graphene oxide (GO) was synthesized via improved Hummers method. Hydrophilic functional groups of GO were replaced with hydrophobic groups of octadecyl amine (ODA), while FTIR examination confirmed the successful decoration of GO with ODA. Hydrophobic GO‐ODA/epoxy nanocomposites with high structural integrity were developed via vacuum shock technique. Developed GO‐ODA/epoxy nanocomposites showed higher resistance against chemical degradation compared with GO/epoxy nanocomposite and pure epoxy resin.